Non-benzoquinone geldanamycin analogs trigger various forms of death in human breast cancer cells. Issue 1 (December 2016) - Zhang, Zhirui; Li, Hong-Mei; Zhou, Can; Li, Qixiang; Ma, Linyan; Zhang, Zixuan; Sun, Yiming; Wang, Lirong; Zhang, Xudong; Zhu, Bing; Hong, Young-Soo; Wu, Cheng-Zhu; et al.
Abstract Background Hsp90 proteins are important therapeutic targets for many anti-cancer drugs in clinical trials. Geldanamycin (GA) was identified as the first natural inhibitor of Hsp90, increasing evidence suggests that GA was not a good choice for clinical trials. In this study, we investigated two new non-benzoquinone geldanamycin analogs of Hsp90 inhibitors, DHQ3 and 17-demethoxy-reblastatin (17-DR), to explore the molecular mechanisms of their anti-cancer activity in vivo and vitro. Methods MTT and colony formation assays were used to measure cell viability. Flow cytometry, DAPI staining, ATP assay, electron microscopy, western blots, siRNAs transfection and immunofluorescence were used to determine the molecular mechanism of DHQ3- or 17-DR-induced different forms of death in human breast cancer MDA-MB-231 cells. Malachite green reagent was used to measure ATPase activity of the analogs. Results DHQ3 and 17-DR presented efficiently inhibitory effect in MDA-MB-231 cell lines, and DHQ3 induced necroptosis by activation of the RIP1-RIP3-MLKL necroptosis cascade. And DHQ3-induced cell death was inhibited by a necroptosis inhibitor, necrostatin-1 (Nec-1), but not by a caspase inhibitor z-VAD-fmk. On the other hand, 17-DR induced apoptosis in MDA-MB-231 cells, indicating a caspase-dependent killing mechanism. We further demonstrated that down-regulation of RIP1 and RIP3 by siRNA protected against DHQ3 but not 17-DR induced cell death. These results were confirmed by electron microscopy. DHQ3 and 17-DR induced the degradation of Hsp90 client proteins, and they showed strong antitumor effects in MDA-MB-231 cell-xenografted nude mice. Conclusions These findings supported that DHQ3 and 17-DR induce different forms of death in some cancer cell line via activation of different pathways. All of the results provided evidence for its anti-tumorigentic action with low hepatotoxicity in vivo, making them promising anti-breast cancer agents.